Triplex Confinium- Liminal Spaces of Transculturation and Hybridization in the Early Modern Period - Blažević, Zrinka (Array, 2014)
The complex character of the contemporary social, political and cultural situation in Croatia is mostly the result of its specific development during the early modern period. It was a transitional historical epoch in which the basic structures and patterns of the "multiple modernities" were gradually formed. The dynamic paradigm of this development was mainly determined by geopolitical factors, i.e. its location on the boundary of three confronting imperial powers: the Habsburg Monarchy, the Venetian Republic and the Ottoman Empire (Triplex Confiniuum), established after the Karlowitz Peace Treaty in 1699. On the ground of the three key postcolonial concepts - liminality, hybridity and transculturation – this paper is aimed at demonstrating how interdisciplinary exchange and mutuality between post-colonial theory and border studies could bring about useful heuristic models and research protocols for the examination of the complex political, social, economic confessional and cultural scenery of the paradigmatic early modern imperial border zone - Triplex Confinium.